Biological pretreatment of corn stover with Phlebia brevispora NRRL‐13108 for enhanced enzymatic hydrolysis and efficient ethanol production. (28th January 2017) - Saha, Badal C.; Kennedy, Gregory J.; Qureshi, Nasib; Cotta, Michael A.
Abstract : Biological pretreatment of lignocellulosic biomass by white‐rot fungus can represent a low‐cost and eco‐friendly alternative to harsh physical, chemical, or physico‐chemical pretreatment methods to facilitate enzymatic hydrolysis. In this work, solid‐state cultivation of corn stover with Phlebia brevispora NRRL‐13018 was optimized with respect to duration, moisture content and inoculum size. Changes in composition of pretreated corn stover and its susceptibility to enzymatic hydrolysis were analyzed. About 84% moisture and 42 days incubation at 28°C were found to be optimal for pretreatment with respect to enzymatic saccharification. Inoculum size had little effect compared to moisture level. Ergosterol data shows continued growth of the fungus studied up to 57 days. No furfural and hydroxymethyl furfural were produced. The total sugar yield was 442 ± 5 mg/g of pretreated corn stover. About 36 ± 0.6 g ethanol was produced from 150 g pretreated stover per L by fed‐batch simultaneous saccharification and fermentation (SSF) using mixed sugar utilizing ethanologenic recombinant Eschericia coli FBR5 strain. The ethanol yields were 32.0 ± 0.2 and 38.0 ± 0.2 g from 200 g pretreated corn stover per L by fed‐batch SSF using Saccharomyces cerevisiae D5A and xylose utilizing recombinant S. cerevisiae YRH400 strain, respectively. This research demonstrates that P. brevispora NRRL‐13018 has potential to be used for biological pretreatment of lignocellulosic biomass. This is the first report on the production of ethanol from P. brevispora pretreated corn stover. © 2017 American Institute of Chemical Engineers Biotechnol. Prog., 33:365–374, 2017